Planetary nebulae associated with galactic star clusters (2021)
ABSTRACT: Obtaining accurate distances to Galactic planetary nebulae (PNe) has proved to be a challenging task. Estimates of the uncertainties in the distances range on average between 30-50%. Association between PNe and stars clusters offers a reliable scenario to determine their fundamental parameters. Up to now, just four PNe have been associated to open clusters (OCs) and four more to Galactic globular cluster (GC). Confirmed associations enable parameters such as age, distance, internal reddening, physical size and progenitor mass of the PNe to be estimated. Furthermore, they allow theoretical models of the star evolution to be evaluated. In this work, we are interested in assessing potential association between five PNe and the same number of OCs, namely, the pairs PN/OC: Hen 2-133/Lynga 5 – Hf 69/Lynga 15 – Wray 17-31/Basel 20 – Wray 17-31, NGC 2899/IC 2488 and NGC 2452/NGC 2453. Intermediate resolution spectra of 72 bright stars of the OCs were collected, as well as for each PN. In addition, new UBV, JHKs and BP-RP) photometry was extracted from VVV-2MASS and Gaia second data release (DR2), respectively. Spectra were used to determine radial velocity (RV) for both OC and PNe. If the RVs disagree, the membership is rejected. But, if they agree, other parameters as distance, reddening, and age need to be evaluated. Photometric and astrometric data were used to obtain new and more accurate cluster parameters. The most open clusters have been poorly studied, thus our first effort was directed to obtain their fundamental parameters. Eleven open clusters were finally studied, six of them lying in the complex vicinity of the OC Lynga 15, which is one of our target clusters. A constraint to the distance of d > 7 kpc for the remote cluster candidate LS 007 was obtained using VVV data. Moreover, the longstanding discrepancy in the distance of the OC NGC 2453 was resolved, as well as the real nature of the OCs Lynga 15, Loden 465, Loden 467, Bica 5 and Basel 20. The latter are not real clusters but probable field starsfluctuations. We finally conclude that the PNe NGC 2452, Hf 69, Hen 2-133 and Wray 17-31 are not members of the OCs NGC 2453, Lynga 15, Lynga 5 and Basel 20/IC 2488, respectively. In contrast, PN Hf 69 shares roughly the same parameters as OC Stock 14 but the youth of the cluster and the angular separation make membership unlikely. Finally, PN NGC 2899 seems to be a strong candidate for being a member of IC 2488 despite the large angular separation (∼54').